2019
DOI: 10.1007/s11482-018-9699-8
|View full text |Cite
|
Sign up to set email alerts
|

Possession and Applicability of Signature Character Strengths: What Is Essential for Well-Being, Work Engagement, and Burnout?

Abstract: Signature character strengths can foster health-related outcomes in work and private life, thus being particularly important for endangered occupational groups like physicians. However, situational circumstances need to allow character strengths demonstration (applicability) first to enable their application. Therefore, this study addresses the role of (1) applicability of signature character strengths in work and private life beyond their possession and (2) relationships with well-being, work engagement, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 60 publications
1
42
0
1
Order By: Relevance
“…Our findings revealed that both groups generally rated the applicability of signature character strengths in private life higher than during studies. Huber et al (2019) reported similar results for a sample of physicians. These findings could be explained by the fact that character strengths and their application are not mentioned or trained in the medical curriculum per se.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Our findings revealed that both groups generally rated the applicability of signature character strengths in private life higher than during studies. Huber et al (2019) reported similar results for a sample of physicians. These findings could be explained by the fact that character strengths and their application are not mentioned or trained in the medical curriculum per se.…”
Section: Discussionsupporting
confidence: 60%
“…Hence, the "Applicability of Character Strengths Rating Scale" ACS-RS (Harzer and Ruch, 2013) was developed to measure the individually perceived influence of four conditions: two external ones: (I) normative demands and (II) appropriateness of strength-related behavior in given situations; two internal ones: (III) perceived presence of factors that may facilitate or hamper strength-related behavior and (IV) intrinsic motivation to show certain behavior Ruch, 2012, 2013). Recently conducted cross-sectional studies with samples of medical students and physicians emphasized the important role of one's applicable signature character strengths (applicability of signature character strengths in the context of study and work = ASCS-S/-W; and private life = ASCS-P) to foster mental health, well-being, burnout and work-engagement (Hausler et al, 2017a;Huber et al, 2019;Strecker et al, 2019). Furthermore, Höge et al (2019) could demonstrate with a sample of hospital physicians that the ASCS-W at the first measurement (T1) had an impact on the perception of the socio-moral climate of the medical department at the second measurement (T2) and reversed effects of the socio-moral climate at T1 on the ASCS at work at T2.…”
Section: Introductionmentioning
confidence: 99%
“…Further, while the current study focused on "possessing" character strengths, most intervention studies aim at increasing the application of strengths (e.g., Seligman et al, 2005). Since, the application and the possession of character strengths have been reported to be relevant for well-being (Huber et al, 2018), future studies might examine the effects of both on longitudinal changes in well-being.…”
Section: Discussionmentioning
confidence: 99%
“…These strengths (groups) may correspond, more or less, to specific work characteristics: e.g., strengths of mind to cognitive demands or interpersonal strengths to social support. Furthermore, the relations to various outcomes are potentially supposed to vary (e.g., Huber et al 2018 in this special issue), also considering, for example, the so called Bhappiness strengths( e.g., Littman-Ovadia et al 2017;Hausler et al 2017b).…”
Section: Discussionmentioning
confidence: 99%